PENGARUH STRUKTUR MODAL, CAPITAL INTENSITY, DAN PROFITABILITAS TERHADAP EFFECTIVE TAX RATE PADA PERUSAHAAN MANUFAKTUR YANG TERDAFTAR DI BURSA EFEK INDONESIA (BEI) - Salma; Ihsan Burhanuddin, Chairul; Said, Saida (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This study aims to analyze the effect of capital structure, capital intensity, and profitability on the Effective Tax Rate (ETR) in manufacturing companies listed on the Indonesia Stock Exchange (IDX) for the 2020–2024 period. ETR is used as an indicator to measure the actual tax burden borne by the company relative to pre-tax profit. This research employs a quantitative approach with panel data regression analysis. The population encompasses all manufacturing companies listed on the IDX, with 50 companies selected as the research sample through purposive sampling, yielding 250 total observations. Secondary data were obtained from annual financial statements published through the IDX official website and analyzed using EViews software. The results indicate that partially, capital structure (DER), capital intensity (CIR), and profitability (ROA) each have a positive and significant effect on ETR. Simultaneous testing confirms that all three variables jointly have a significant effect on ETR (F-statistic = 36.98, prob. = 0.000). These findings indicate that increases in capital structure, fixed asset intensity, and profitability tend to increase the effective tax burden, consistent with agency theory and the regulatory context of Indonesia’s tax reform. Companies therefore need to optimally manage their financing, asset investment, and earnings performance to achieve tax efficiency.